Properties of glass-ceramics in li20-al20 3-si02 (Las) system with ti02 as nucleating agent - Sawhney T.R.; Joshi V.C.; Singh N. (My University, 2025)
A glass composition of' Li20-15, Al20 3-ll, Si02-74 wt% doped with 16 parts of Ti02 per 100 parts of glass was melted and heat treated at 550° and 850°C, considered to be nucleation and crystallization temperatures respectively on the basis of DTA of coarse and fme grains of glass. XRD (X-ray diffraction pattern) of the glass ceramics showed the presence of Li20.AI20 3.8Si02 and Li20.AI20 3.4Ti02 as the major crystalline phases in it. Thermal elongation of glass ceramics showed some discontinuity close to 300°C indicating two ditferent types of phase assembleges contributing to elongation. Durability and density of the glass-ceramics showed chang; from 9.3 mg of H2S04 to 0.51 mg of H2S04 (consumed during titnttinn) and from 0.01% to 1.17% respectively. © 1995 Taylor and Francis Group, LLC.